Traditional ecological knowlegde and biodiversity management in the Andes of southern Ecuador - Pohle, Perdita; Gerique-Zipfel, Andres (Geographica Helvetica, 2006)
The tropical mountain rainforests of the eastern Andean slopes in southern Ecuador have an extraordinary rich biodiversity. At the same time. these sensitive ecosystems are vulnerable because of the extension of agricultural land, the extraction of timber, mining activities, the tapping of water resources and similar anthropogenic intrusions. Ethno-specific knowledge of the tropical rainforest ecosystem was determined in sample communities of the Shuar, the Saraguros and the Mestizo-Colonos – particularly with respect to the natural forest resources and their uses. Ethnoecological and agrogeographical research methods were used to document the indigenous knowledge of traditionally utilized wild and eultivated plants, to analyze current forms of land use (including the traditional cultivation of forest and home gardens), and to evaluate ethno-specific survival strategies and strategies of biodiversity managemen
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IG.LGIPDH.tradit